Impaired function of regulatory T cells in cord blood of children of allergic mothers - Hrdý, J; Kocourková, I; Prokešová, L (Clinical and experimental immunology, 2012)
Allergy is one of the most common diseases with constantly increasing incidence. The identification of prognostic markers pointing to increased risk of allergy development is of importance. Cord blood represents a suitable source of cells for searching for such prognostic markers. In our previous work, we described the increased reactivity of cord blood cells of newborns of allergic mothers in comparison to newborns of healthy mothers, which raised the question of whether or not this was due to the impaired function of regulatory T cells (T(regs)) in high-risk children. Therefore, the proportion and functional properties of T(regs) in cord blood of children of healthy and allergic mothers were estimated by flow cytometry. The proportion of T(regs) [CD4(+)CD25(high)CD127(low) forkhead box protein 3 (FoxP3(+))] in cord blood of children of allergic mothers tends to be higher while, in contrast, the median of fluorescence intensity of FoxP3 was increased significantly in the healthy group. Intracellular presence of regulatory cytokines interleukin (IL)-10 and transforming growth factor (TGF)-beta was also higher in T(regs) of children of healthy mothers. Although we detected an increased proportion of T(regs) in cord blood of children of allergic mothers, the functional indicators (intracellular presence of regulatory cytokines IL-10 and TGF-beta, median of fluorescence intensity of FoxP3) of those T(regs) were lower in comparison to the healthy group. We can conclude that impaired function of T(regs) in cord blood of children of allergic mothers could be compensated partially by their increased number. Insufficient function of T(regs) could facilitate allergen sensitization in high-risk individuals after subsequent allergen encounter.
Keywords: těhotenství; forkhead transkripční faktory; receptor interleukinu-7 - alfa-podjednotka; fetální krev; lidé; průtoková cytometrie; T-Lymphocytes, Regulatory; Case-Control Studies; antigeny CD4; Female; Flow Cytometry; regulační T-lymfocyty; Transforming Growth Factor beta; Humans; Infant, Newborn; receptor interleukinu-2 - alfa-podjednotka; transformující růstový faktor beta; Interleukin-10; studie případů a kontrol; alergie; interleukin-10; Forkhead Transcription Factors; novorozenec; Pregnancy; ženské pohlaví; CD4 Antigens; Interleukin-7 Receptor alpha Subunit; Hypersensitivity; Interleukin-2 Receptor alpha Subunit; Fetal Blood